Profitability, PPN PMSE Exposure, and Tax Avoidance: The Moderating Role of ESG Disclosure - Abdillah Daim, Ahmad Ridlo; Srikalimah; Niam, M. Alfa (Jurnal Manajemen, 2026)
This syudy aims to analyse the influence of profitability and PPN PMSE exposure on tax avoidance, and to assess the moderating role of ESG disclosure among PPN PMSE collection companies registered with the Directorate General of Taxes (DJP). The sample comprises 17 companies from 2022 to 2024 (51 firm-year observations). Secondary data were collected from annual financial reports, GRI-based sustainability reports, and DJP documents, then analyzed using panel regression and moderated regression with the Moderated Regression Analysis (MRA) approach. The results indicate that: (i) profitability has no significant effect on tax avoidance; (ii) PPN PMSE exposure is also not significant; (iii) ESG disclosure has a significant negative effect on tax avoidance; however, (iv) ESG disclosure does not moderate the relationship between profitability or PPN PMSE exposure and tax avoidance. The findings suggest that transparency in sustainability reporting is associated with reduced tax aggressiveness, while PPN PMSE policy requires stronger oversight to influence fiscal behavior. This research contributes to understanding how environmental, social, and governance transparency can impact tax strategies, informing policymakers and corporate managers on the importance of disclosure practices.